Efektivitas Relaksasi Zikir Untuk Menurunkan Tingkat Stres Pada Remaja Diabetes Melitus Tipe II - Saulia Safitri; Fuad Nashori; Indahria Sulistyarini (JIP (Jurnal Intervensi Psikologi), 2017)
Diabetes is one of the important causes of stress experienced by the diabetes patients. Relaxation as a respon of dhikr could enhance health and well being of diabetes patience. The hypothesis of the research is that relaxation with Dhikr could decrease stress among type II diabetes patients. Relaxation with Dhikr is a combination from relaxation technique and Dhikr (remembrance of God). The subjects of the research were 15 diabetes patients and classified into experimental and control group. Research method was the untreatedcontrol group design with pretest dan postest. This intervention consist of 2 meeting sessions with 13 materials. Before the therapy, the participants fill the stress scale as the screening process. Data from both group analyzed with independent sample t test.The results showed that there were significant different of stress stage between the control group and experimental group, which p=0,014 (p,0,05). The result indicates that the relaxation of dhikr decreased stress among type II diabetes patients.Key Words: Stress, relaxation of dzikr, type II diabetes milletus